Contribuições dos aspectos culturais na implementação do planejamento estratégico - Sarturi, Greici (2011)
The strategic planning corresponds to a management tool widely used by the organizations. However, the implementation of such tool may bring about structural changes on the enterprise organization. Due to those changes, to start a formulation and strategic implementation it is necessary to take into consideration aspects related to the organization culture, because just as the cultural aspects are influenced by the changing process, they also influence on the strategic decisions. For the need of gathering information on the organization culture which enable the increasing on the Strategic Planning effectiveness , this research has the aim to identify and examine the cultural aspects which contribute to the implementation of the Strategic Planning. To achieve the proposed objective it was used the case study methodology, of qualitative approach and descriptive literature. Data were collected through semi-structured interviews whose analysis was accomplished through methodology suggested by Moraes (2003). The cultural aspects were studied based on the Trompenaars (1994) patterns, who suggests the culture profile analysis in an organization through seven extents, being five of them related to relationships and rules, one about the way the enterprise manages the time and another about the way it relates with nature. The obtained results evidenced that the cultural aspects constitute an important study variable when it is intended to use a management tool. Concerning the Strategic Planning the extents Universalism versus Particularism; Collectivism versus Individualism; Diffuse versus Speciffic; Synchronous versus Sequential were the ones which revealed the biggest influence concerning the tool effectiveness.